MUC1 (CA27.29) before and after Chemotherapy and Prognosis in High-Risk Early Breast Cancer Patients - Hübner, Hanna; Häberle, Lothar; Müller, Volkmar; Schrader, Iris; Lorenz, Ralf; Forstbauer, Helmut; Fink, Visnja; Schochter, Fabienne; Bekes, Inga; Mahner, Sven; Jückstock, Julia; Nabieva, Naiba; et al. (Cancers, 2022)
Soluble MUC1 has been discussed as a biomarker for predicting prognosis, treatment efficacy, and monitoring disease activity in breast cancer (BC) patients. Most studies in adjuvant settings have used preoperative assessment. This study, part of the SUCCESS-A trial (NCT02181101), assessed the prognostic value of soluble MUC1 before and after standard adjuvant chemotherapy. Patients with high-risk BC were treated within the SUCCESS-A trial with either three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide followed by three cycles of docetaxel or three cycles of FEC followed by three cycles of docetaxel and gemcitabine. Cox regression analyses were performed to investigate the prognostic value of CA27.29 before and after chemotherapy relative to disease-free survival (DFS), along with established BC prognostic factors such as age, body mass index, tumor size, nodal status, estrogen receptor, progesterone receptor, HER2 status, and grading. Pre-chemotherapy and post-chemotherapy CA27.29 assessments were available for 2687 patients of 3754 randomized patients. Pre-chemotherapy CA27.29 assessment was associated with DFS in addition to established prognostic factors. It had no prognostic value in node-negative patients, but there was a clear association in node-positive patients. Post-chemotherapy CA27.29 assessment did not add any prognostic value, either on its own or in addition to pre-chemotherapy CA27.29 assessment.
CRIS-Team Scopus Importer:2022-04-08
Keywords: anthracycline; CA15-3; CA27.29; chemotherapy; early breast cancer; MUC1; taxane; tumor marker